A study on the efficacy of eudaimonic well-being group counseling to develop empathy in high school students involved in brawling and klithih in Yogyakarta - Sutanti, Tri; Suherman, Uman; Ilfiandra, Ilfiandra (Universitas Ahmad Dahlan, 2025)
This study aims to test the effectiveness of the eudaimonic wellbeing group counseling model to develop empathy in students involved in brawls and klithih in high schools in Yogyakarta city. The type of research used in this study is experimental research with a pre-experimental design approach, using a one group pretest-posttest design model. The sampling technique used was purposive sampling, namely students who were known to have been involved in brawls and klithih totaling seven people, and are currently still attending one of the high schools in Yogyakarta City in grade eleven. The instrument used to collect data was an empathy scale, which consists of two main components, namely cognitive empathy and empathy affective. Data were analyzed using the Paired Sample T-Test. The results of the study showed that the eudaimonic wellbeing group counseling model given for eleven sessions has been proven effective in increasing empathy in students involved in brawls and klithih in high schools in Yogyakarta city. The results of this study can be used as an alternative counseling strategy for school counselors as a preventive and curative effort in character development, especially instilling empathy values in students involved in brawls and klithih.